The relationship between emotional self-awareness, emotion regulation, and diabetes distress among Italian and Dutch adults with type 1 diabetes - Bassi, Giulia; Embaye, Jiska; de Wit, Maartje; Snoek, Frank J.; Salcuni, Silvia (Frontiers in Psychology, 2023)
Objective: Evidence suggests that many adults with type 1 diabetes (T1D) experience clinically relevant levels of diabetes distress, indicating coping difficulties. Studies have primarily focused on emotion regulation as a possible construct to be addressed in psychological interventions to alleviate diabetes distress. This study extends the literature by investigating the cross-sectional association between emotion regulation, diabetes distress and the construct of emotional self-awareness as an additional variable to be considered in potentially reducing diabetes distress. Methods: Via an online survey, data was collected on emotional self-awareness dimensions (attention to feelings, clarity of feelings), emotion regulation strategies (cognitive reappraisal, expressive suppression, mood repair) and diabetes distress, along with self-reported clinical and sociodemographic information. Multiple linear regression with stepwise backward method was used to examine associations, controlling for country. Results: N = 262 Italian and Dutch adults with T1D (80.5% women, M = 38.12 years, SD = 12.14) participated. Clarity of feelings was significantly negatively associated with diabetes distress, resulting in a medium effect size (β = -0.22, p < 0.001). Likewise, mood repair was negatively related to diabetes distress, showing a small effect size (β = -0.26, p < 0.001). Conclusions: These findings shed light on the importance of a dimension of emotional self-awareness, namely clarity of feelings. This represents the ability to identify one's emotional states and discriminate between them. Thus, it should be considered in psychological interventions, such as mentalization-based treatment, that might contribute to alleviating T1D-related distress.